Turismo em Cabo Verde : um estudo da competitividade entre os clusters de Santo Antão-São Vicente e Sal-Boa Vista - Fortes, Valter Marcos Monteiro (My University, 2014)
Joint efforts between firms are increasingly common, even when there exists competitive rivalry in the market. Companies tend to group together in (I erased what was written here) clusters, forming critical masses of industries to take advantage of synergies such as increased productivity, innovation and, in essence, the possibility of becoming more competitive. Given that clusters increase the competitiveness of an industry and given that tourism is a powerful instrument of regional development, this study is aimed at examining the determinants of competitive advantage for tourism clusters of Santo Antao - Sao Vicente and Sal - Boavista, which are a set of four islands located in the Republic of Cape Verde, Africa. In order to identify the relevant variables to enhance competitiveness in these regions, a semi-structured model was created in light of the "Diamond of Competitiveness" by Porter (1990). It incorporated the following attributes: (i) factor conditions, (ii) demand conditions, (iii) strategy, structure and rivalry of the companies, (iv) related and supporting industries, and the influence of the government variable. The Government´s role was evaluated from the national level whereas this can influence significantly the determinants of competitive advantage. Thus, the operationalization of this study was through a quantitative survey, with data analysis using the statistical procedure called the Mann Whitney. Data from field research resulted in a sample of 100 businesses, hotels, restaurants, travel agencies, sports and recreation, clubs, lodging and rental car, which was proportionally divided between the two clusters. Results from the application of the model indicate the competitive performance of tourism in each of the clusters thus infer theoretical and empirical implications, and the resulting managerial implications that favor the goals of both public and private sector aimed at improving the competitiveness of the clusters under study . It is still possible through a comparative basis of variables foster learning from one region over another in order to introduce improvements.
Os esforços conjuntos entre empresas são cada vez mais comuns, mesmo que exista rivalidade competitiva no mercado. Empresas tendem a se agrupar no que vem a ser conFigurado como cluster, formando massas críticas segmentos da indústria para aproveitar a sinergia como o aumento da produtividade, inovação e, em sua essência, a possibilidade de se tornarem mais competitivas. Dado que os clusters aumentam a competitividade de uma indústria e dado que o turismo constitui um poderoso instrumento de desenvolvimento regional, o presente estudo teve como objetivo analisar os determinantes da vantagem competitiva dos Clusters turísticos de Santo Antão - São Vicente e Sal - Boavista que são um conjunto de quatro ilhas situadas na Republica de Cabo Verde África. A fim de identificar quais as variáveis relevantes para aperfeiçoar a competitividade nestas regiões foi aplicado um questionário semi-estruturado sob a luz do modelo do Diamante da Competitividade de Porter (1990), contemplando os atributos: (i) condições dos fatores, (ii) condições da demanda, (iii) estratégia, estrutura e rivalidade da empresas, (iv) setores correlatos e de apoio; e ainda a variável Governo. O papel do Governo foi avaliado a partir da esfera nacional considerando que este pode influenciar, de forma significativa, os determinantes da vantagem competitiva. Assim, a operacionalização deste estudo foi mediante uma pesquisa quantitativa, com a análise dos dados através do procedimento estatístico chamado de Mann Whitney. Os dados provenientes da pesquisa de campo, resultaram de uma amostra de 100 empresas hotéis, restaurantes, agências de viagem, esportes e recreação, discotecas, alojamentos e locadora de veículos - que foi proporcionalmente dividida entre os dois clusters. Os resultados decorrentes da aplicação do Modelo indicam o desempenho competitivo turístico de cada um dos clusters permitindo assim inferir implicações teóricas e empíricas, bem como as decorrentes implicações gerenciais que favorecem os objetivos tanto de ordem pública como privada visando o aperfeiçoamento da competitividade nos clusters em estudo. Ainda é possível através de uma base comparativa das variáveis analisadas fomentar o aprendizado de uma região em relação a outra com o intuito de instituir melhorias.
Keywords: Administração; Cluster; Turismo; Cabo Verde; São Vicente, Ilha de (Cabo Verde); Santo Antão, Ilha de (Cabo Verde); Sal, Ilha do (Cabo Verde); Boa Vista, Ilha da (Cabo Verde); Diamante da competitividade; Cluster; Tourism; Cape Verde; Santo Antão Island (Cape Verde); São Vicente Island (Cape Verde); Sal (Cape Verde); Boa Vista Island (Cape Verde); Competitiveness Diamond